2015
DOI: 10.1039/c5an01088h
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical DNA sensor based on polyaniline/graphene: high sensitivity to DNA sequences in a wide range

Abstract: A label-free electrochemical DNA sensor was fabricated by deposition of polyaniline and pristine graphene nanosheet (P/G(ratios)) composites in different mass ratios, DNA probe and bovine serum albumin (BSA) layer by layer on the surface of a glassy carbon electrode (GCE). Electrochemical impedance spectroscopy (EIS) was employed to monitor every step of fabrication of P/G(ratio)-based DNA sensors and to evaluate the detection results in terms of the hybridization of complementary DNA, mutant DNA and non-compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 46 publications
(94 reference statements)
0
17
0
Order By: Relevance
“…Two-dimensional (2D) graphene offers large surface area for immobilization of biomolecules and fast electron transfer rate [30][31][32]. Single-stranded DNA (ssDNA) can be stably immobilized on graphene surface through π-π stacking interaction between the conjugated π bonds of nucleotide bases and the hexagonal units of graphene [33,34], which is beneficial for electrochemical biosensing applications. Additionally, more and more attention has been paid to three-dimensional (3D) graphene, because the 3D macroporous structures are able to provide more sufficient adsorption space and contact area between electrolyte and electrode to further enhance the property and broaden the applications of graphene [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) graphene offers large surface area for immobilization of biomolecules and fast electron transfer rate [30][31][32]. Single-stranded DNA (ssDNA) can be stably immobilized on graphene surface through π-π stacking interaction between the conjugated π bonds of nucleotide bases and the hexagonal units of graphene [33,34], which is beneficial for electrochemical biosensing applications. Additionally, more and more attention has been paid to three-dimensional (3D) graphene, because the 3D macroporous structures are able to provide more sufficient adsorption space and contact area between electrolyte and electrode to further enhance the property and broaden the applications of graphene [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…For 3-MPA SAM substrate electrode, both current of anodic peak (I pa ) and cathodic peak (I pc ) have a little decrease and the separation potential between anodic peak and cathodic peak (ΔE p ) becomes bigger than the bare Au substrate electrode. In the experiment of EIS, the Randles equivalent circuit[28] was used to fit EIS data and determine the charge transfer resistance (R ct ). The EIS curves show that the R ct value of 3-MPA SAM electrode (282.1 ohm) is slightly higher than the bare electrode (254.6 ohm).…”
mentioning
confidence: 99%
“…Du et al, on the other hand, reported a DNA biosensor based on electrochemically reduced GO and PANI nanofibers, with noncovalently assembled oligonucleotide probes and [Ru(NH 3 ) 6 )] 3+ as a redox marker. More recently, Zheng et al prepared pristine graphene PANI nanocomposites at various mass ratios, via solution mixing and casting, followed by oligonucleotide probe adsorption and bovine serum albumin adsorption, aimed at minimizing nonspecific signal . By tuning the graphene PANI mass ratio it was possible to adjust the detection limit and dynamic range.…”
Section: Biorecognition Interfacesmentioning
confidence: 99%